Utilization of coconut shell waste into charcoal briquettes in Sungai Kupah Village, Kubu Raya Regency - Ely Nurhidayati; Erni Yuniarti; Nana Novita Pratiwi; Agustiah Wulandari; Firsta Rekayasa Hernovianty (University of Merdeka Malang, 2022)
The target villages located in Sungai Kupah Village, Sungai Kakap District, Kubu Raya Regency, West Kalimantan have potential in the agricultural sector, especially in the primary sector, namely coconut plantations. Most of the coconut harvest in Sungai Kupah Village only uses the flesh of the fruit which is processed as copra. Other parts such as shells and coconut husks are just thrown away, piled up, and not used. Therefore, the village development program can be an opportunity for the community to be able to process, utilize and increase the added value of coconut fruit products and coconut waste. This program is implemented by applying the offline method while still observing health protocols during the Covid-19 pandemic. The lecturer team and the student team carry out full community development and empowerment activities in the field using facilities, such as a hall as a place for socialization and training. The prospective development is coconut waste into charcoal briquettes. The implementation of this village development program is called PDKMI Briketku: Program Desa Kupah Mandiri Industri Arang Briket. As for the activities of the PDKMI